The Correlation between Students’ Instrumental Motivation and their English Achievement at Al Azhar Center Baturaja - Salsabila; Novarita; Trisilia Devana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
This study aims to find out whether any correlation between students’ instrumental motivation and their English achievement at MA Al- Azhar Center Baturaja. The type of this research was correlational design. The data was gathered from 100 out of 313 students, representing 30% of the population, through questionnaires and documentation. This questionnaire consist of 20 items into 6 indicator for instrumental motivation. For the documentation took the odd semester report card grades of English Subject. In class X.D, showed high motivation and good English achievement, with strong correlation. In class XI.C, showed high motivation and good English achievement, with low correlation. In class XI.D, showed high motivation and good English achievement, with moderate correlation. In class XII.D, showed very high motivaton and very good English achievement, with low correlation. Overall, students at MA Al-Azhar Center Baturaja showed high motivation and good English achievement. Thus, the overall results of the study confirmed that high category of motivation correlated with good English achievement. The result of analysis found a correlation between students' instrumental motivation and their English achievement at MA Al-Azhar Center Baturaja. The analysis revealed a strong correlation (coefficient of 0.634, p < 0.05), supporting the acceptance of the alternative hypothesis and rejection of the null hypothesis.